PERANCANGAN SISTEM AKUNTANSI PENJUALAN PADA UD. BLESS - Andreuw Kristian Pantow; Sintia Nurani Korompis; Esrie A. N. Limpeleh; Elisabeth Deisi Malonda; Alfrets Daleno (Journal of Information System, Applied, Management, Accounting and Research, 2023)
This study aims to design a sales accounting system at UD Bless with a flowcharts that is expected to provide transaction information in the revenue cycle. The research method was qualitative. Instruments of data collection was down through interview in the form of questions regarding the sales system. While the data collection instrument with documentation, was done through namely evidence of transactions that occurred in the business. The results of the study are the design of a sales accounting system which consists of designing organizational structures, procedures for cash and credit sales using document flowcharts, and design of accounting records to provide financial information needed by internal parties of the entity. Keywords: component; formatting; style; styling; insert (Minimum 3 to 5 key words)